Informal Economy, Institutional Quality, and Socioeconomic Conditions in Lampung Province, Indonesia - Rismiyanti Nurul Amelia; Rizki Dini Meylani; Irmayani Irmayani; Kadek Via Purnamasari; Daffa Dyaulhaq (Edumaspul: Jurnal Pendidikan, 2024)
This study examines the relationship between the informal economy, institutional quality, and socioeconomic outcomes in Lampung Province, Indonesia. It adopts a rigorous methodological framework using Fully Modified Ordinary Least Squares, Quantile Regression, and Dynamic Threshold Analysis to analyze balanced district-level panel data covering the years 2010 to 2023. The findings reveal that informal economic activity exerts a negative influence on regional welfare, particularly in districts with weak institutional performance. In contrast, stronger institutional quality is associated with more favorable socioeconomic conditions. The analysis identifies a critical value of the Institutional Quality Index at 5.2, above which the negative effects of informality are significantly reduced. These results emphasize the crucial role of institutional development in mitigating the adverse consequences of informal economic activity and advancing inclusive regional progress. To ensure analytical rigor, the study incorporates comprehensive diagnostic testing and confirms the reliability and validity of its constructs through consistency checks across variables, normalization procedures, and robustness assessments across multiple models